KARAKTERISTIK COOKIES TEPUNG KIMPUL TERMODIFIKASI (Xanthosoma sagittifolium) DENGAN PENAMBAHAN TAPIOKA - Dedin Finatsiyatull Rosida; Nindya Aulia Putri; Maghfiroh Oktafiani (AGROINTEK, 2020)
Cookies are processed cakes made from wheat flour. However, currently the need for flour is mostly met with import activities, so there needs to be an effort to reduce dependence on the use of wheat flour. One of the local food resources that can be used as an alternative to flour is cocoyams flour (Xanthosoma sagittifolium) which was modified by the fermentation process using the starter Lactobacillus plantarum to improve product texture. Tapioca can also be used as a substitute for wheat flour in making cookies, while the formation of texture can be helped by the addition of margarine. This study aimed to determine the effect of the proportion of cocoyams flour: tapioca flour and the addition of margarine to the characteristics of cookies. This research used factorial completely randomized design with two factors. The first Factor is proportion of modification cocoyams flour and   tapioca (50:50, 60:40, and 70:30). The second factor in the form of concentration addition of margarine (50%, 60%, 70%). The results showed that the best treatment was the proportion of modification cocoyams and tapioca flour (70:30) and the addition of 50% margarine which produced cookies with criteria of water content of 3.95%, fat content of 29.15%, crude fiber of 3.29%, fracture strength of 11.17 N, yield of 55.95%, and organoleptic test results with the number of ranks of preference level for crispness/texture of 139, aroma 110.5, color 106 and taste 133.8